Teknik Peliputan dan Pengembangan Salam TV dan Radio Ar-Risalah 95.7 FM - Winda Kustiawan; Ayu Sawitri; Niatul Mukarramah; Chaerona Artha Lubis; M. Susanto Syahputra Manaor (Universitas Muhammadiyah Enrekang, 2022)
Communication is a basic trait possessed by humans. With communication, humans can relate to each other to fulfill their activities in daily life, for example at work or wherever humans are. Humans are social creatures, so communication is important in everyday life. Media in da'wah is a very important component to achieve the goals and objectives of da'wah. In today's modern era, da'wah interpreters should take advantage of existing technology to facilitate the goals and objectives of their da'wah. If you don't take advantage of the existing media, da'wah will not progress. Media is a way to transfer information from its source to the person or object it is intended for. Media communication is communication that uses channels or means to send messages to people who are far away or in large numbers. There are many types of communication media used, ranging from traditional to modern. For example, kentongan, drums, art performances, newspapers, bulletin boards, magazines, films, radio and television.